Arthropod pests of horticultural crops in tropical Asia - Muniappan, R. (Wallingford, Oxfordshire, UK : CABI, 2012)
Covers the main arthropod pests of twenty five major crops in tropical Asia, with photographs of their adult and immature stages, their distribution, biology, disease vectors, symptoms of the damage they cause and their natural enemies. This book is suitable for researchers, and policy makers of entomology, pest control and crop protection
1. Arthropod pests and their natural enemies on horticultural crops in tropical Asia -- 2. Pests of major vegetable crops -- 3. Pests of minor vegetable crops -- 4. Pests of major fruit crops -- 5. Pests of minor fruit crops -- 6. Pests of other crops
Includes bibliographical references (p. 139-144) and index
Keywords: Arthropod pests -- Asia; Horticultural crops -- Diseases and pests -- Asia